The Associations Of Maternal Emotion Dysregulation And Early Child Dissociative Behaviors. Issue 2 (14th March 2020) - Lewis, Jenn; Binion, Grace; Rogers, Madeline; Zalewski, Maureen
ABSTRACT: Although dissociation is believed to develop in early childhood, there is little research prospectively examining childhood dissociation or parental contributions related to its development. The current study sought to examine parent factors prospectively related to changes in dissociation symptoms in childhood. The current study sampled 68 mother-child dyads at two time points, when children were 3–4 and then 5–6 years, in which mothers with emotion dysregulation were oversampled. Maternal emotion dysregulation was assessed at both time points. Maternal dissociation was assessed only at time two. Child dissociation was assessed at each time point using a modified subscale of the Child Behavioral Checklist. Results showed moderate stability in childhood dissociation across time points. Further, maternal emotion dysregulation and dissociation were both significantly correlated with children's dissociation. Accounting for several covariates, time one maternal emotion dysregulation was prospectively associated with preschoolers' dissociative behaviors at 5–6 years old. The present work suggests that symptoms of dissociation can be observed early in childhood and that maternal factors play an early role in the development of dissociation in children.